Moral Endogeneity Of Love, Trust, And Consciousness In Islamic Economics Of Cooperation Contrary To Their Moral Exogeneity In Neoliberal Theory Of Economics - Masudul Alam Choudhury (CV. SPDF Harmony, 2025)
Background: The conceptual triad of Love, Trust, and Consciousness occupies a central role in shaping socio-economic systems. In the Qur’anic methodological worldview, these elements are intrinsically integrated with material reality through the Tawhidi (monotheistic) law of unity of knowledge, forming an endogenous foundation for cooperation. By contrast, neoliberal economics externalizes ethical considerations, positioning them as exogenous to material processes, which fosters competition, systemic conflict, and distributive injustice. Aims: This study seeks to articulate the ontological and epistemological framework of cooperation within Islamic economics, rooted in the Tawhidi paradigm, and to critically contrast it with the competitive, self-interest-driven paradigm of mainstream economic theory. Methods: Adopting a mesoscience approach, the research develops a model of circular causation and pervasive complementarities, wherein moral and material variables are simulated within a composite wellbeing function. The analysis juxtaposes Qur’anic cooperative principles with the optimization and equilibrium constructs central to neoclassical economics. Results: The findings reveal that the Tawhidi framework consistently generates positive inter-variable complementarities, thereby enhancing the wellbeing criterion and sustaining resource regeneration. Unlike neoliberal competition, which erodes trust and equity, the cooperative paradigm aligns with the maqasid al-shari’ah by promoting justice, equality, and global brotherhood. Conclusion: The study concludes that the Qur’anic law of unity of knowledge provides a superior epistemic and methodological foundation for achieving holistic and sustainable wellbeing. By embedding Love, Trust, and Consciousness within economic relations, it dismantles the scarcity-based logic of marginal productivity, optimality, and steady-state equilibrium. In its place emerges an evolutionary model of resource abundance, institutional complementarity, and moral-material integration. This paradigm not only fulfills the ethical imperatives of Islamic economics but also offers a viable, empirically grounded alternative for addressing contemporary global challenges in justice, equity, and planetary stewardship.